PHYSICAL AND RESERVOIR PROPERTIES PREDICTION FOR RESERVOIR ROCKS IN UNCONVENTIONAL GAS-BEARING GEOLOGICAL STRUCTURES - Skakal's'ka, L. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Research into the behavior of elastic waves in thin-layered gas-bearing geological structures depends on the choice of geophysical and mathematical models of natural geological media and the numerical methods of problem solving. Hence the efficiency of a quasi-homogeneous, isotropic fractured-porous two-phase medium with given physical and mechanical properties. We have suggested a method of calculating empirical relationships between volumetric compression, porosity and pressure in porous rocks of an arbitrary geological region. Data on Zaluzhany wells were used to calculate the correlation and empirical relationships between reservoir properties and parameters of elastic waves and to distinguish dry and oil-gas saturated rocks. The least square technique made it possible to determine the correlation between the compressibility factor of fluid-saturated rocks and their porosity and pressure. Discrimination between oil and water was based on the density parameter. An algorithm has been suggested to do the corresponding calculations. The theoretical and practical implications of this study are as follows: – developing a numerical analytical predictive model for interpreting acoustic data on thin-layered rocks which is based on the correlations between their dynamic physical (effective wave propagation velocities, amplitude attenuation coefficients and their energy absorption) and reservoir (porosity, fracturing, compressibility) properties; – applying the proposed model and software products in geophysical exploration to interpret the geological and geophysical data on the structure and physical characteristics of sections and the physical properties of gas-bearing basins. In seismic acoustic exploration, the numerical model has to include experimental geological and geophysical data on the peculiarities of rock occurrence in the investigated area, with the physical and mechanical properties of different territories showing considerable variation. Such input data, as well as structural features and scattering properties of rocks (density, bedding, microporosity), ensure a significant increase in the accuracy of the numerical analysis. Preliminary testing was based on the data on the elastic moduli and S-wave velocities for dry and fluid-saturated rocks. Calculations were made of the elastic moduli and P-wave velocities for dry and fluid-saturated rocks of the Western oil and gas region of Ukraine (Zaluzhany-18 and Zaluzhany-19 wells). The aim of this work was to demonstrate the efficiency of the predictive method by examining the reservoir rock properties of the wells and to evaluate their gas saturation using the acoustic logging, geophysical and petrophysical data.
Keywords: elastic waves thin-layered rocks seismic acoustic